Digitalisation for agriculture: The case of MUIIS Uganda - ASIGMA Capital (Technical Centre for Agricultural and Rural Cooperation, 2019)
The case of MUIIS project is an epitome of digitalisation for agriculture in which access to digital solutions by smallholder farmers and other value chain actors has led to more efficient operations within the agricultural innovation system, resulting in equal access to finance by women, men, young and old; increased resilience; improved production and income.